Innovative Research on Digital New Media in Corporate Brand Communication - Ziyu Wang (SHS Web of Conferences, 2023)
The development of science and technology has brought us digital new media technology, which has led to the leapfrog development of brand communication methods and opened up new ideas and methods for corporate brand communication. The modern business environment is changing rapidly, and corporate brand communication is also facing huge challenges while welcoming its golden age of development.